The relationship between transformational leadership style, job satisfaction, and employee retention among healthcare workers in hospitals during COVID-19 Crisis. - Raed Hussam Alzoubi; Baker Gamel Shnaikat; Mohammad Yousef Alzaatreh (Universitas Internasional Batam, 2023)
The COVID-19 crisis has presented unique challenges for hospitals and healthcare workers around the world. In this context, transformational leadership may be an important factor in promoting job satisfaction and employee retention during the COVID-19 crisis. The purpose of this paper is to analyze the existing literature to examine the relationship between transformational leadership and employee retention in the context of hospitals, considering the role of job satisfaction as a mediator and developing a conceptual framework between these variables. Searching the database initially yielded 150 articles and after careful examination and application of inclusion criteria, it was reduced to 17 articles which were included in the review. Four themes were generated. This study concluded that leaders who exhibit transformational leadership behaviors have been more successful in maintaining high levels of job satisfaction and employee retention among their staff compared to those with leaders who exhibit transactional leadership behaviors, which focus on rules and regulations.